Androgen-dependent and DNA-binding-independent association of androgen receptor with chromatic regions coding androgen-induced noncoding RNAs. Issue 10 (23rd July 2021) - Sawada, Takahiro; Nishimura, Koichi; Mori, Jinichi; Kanemoto, Yoshiaki; Kouzmenko, Alexander; Amano, Rei; Hayakawa, Akira; Tokiwa, Suguru; Shimmura, Hiroaki; Kato, Shigeaki
ABSTRACT: Androgen induces the binding of its receptor (AR) to androgen-responsive elements (AREs), while genome-wide studies showed that most androgen-induced AR binding sites on chromatin were unrelated to AREs. Enhancer RNAs (eRNAs), a class of noncoding RNAs (ncRNAs), are transcribed from superenhancers (SEs) and trigger the formation of large ribonucleoprotein condensates of transcription factors. By in silico search, an SE is found to be located on the locus of KLK3 that encodes prostate specific antigen. On the KLK3 SE, androgen-induced expression of ncRNAs was detected and designated as KLK3 eRNAs in LNCaP cells, and androgen-induced association of AR and FOXA1 on the KLK3 eRNA coding regions was detected. Such androgen-induced association of an AR mutant lacking DNA binding activity on the KLK3 eRNA coding regions was undetectable on an exogenous ARE. Thus, the present findings suggest a molecular basis of androgen-induced association of AR with chromatin on ARE-unrelated sequences. Graphical Abstract: